30 years of CNES parabolic flights for the benefit of the scientific community - Rouquette, Sébastien (Comptes Rendus. Mécanique)
Parabolic flights allow short microgravity investigations in Physical and Life Sciences, technology and instrumentation tests. The use of parabolic flights is complementary to other microgravity carriers, and preparatory to manned space missions onboard the International Space Station and other manned spacecraft, around the Earth or beyond, to the Moon for example.The main advantages of parabolic flights for microgravity investigations are the short turn-around time, the relatively low cost, the flexibility of experimental approach, the possibility of direct intervention by investigators on board the aircraft during and between parabolas, and the possibility of modifying the experiment set-up between flights.